Methodological standards for in vitro models of epilepsy and epileptic seizures. A TASK1-WG4 report of the AES/ILAE Translational Task Force of the ILAE - Raimondo, Joseph V; Heinemann, Uwe; de Curtis, Marco; Goodkin, Howard P; Dulla, Chris G; Janigro, Damir; Ikeda, Akio; Lin, Chou-Ching K; Jiruska, Premysl; Galanopoulou, Aristea S; Bernard, Christophe (Epilepsia, 2017)
In vitro preparations are a powerful tool to explore the mechanisms and processes underlying epileptogenesis and ictogenesis. In this review, we critically review the numerous in vitro methodologies utilized in epilepsy research. We provide support for the inclusion of detailed descriptions of techniques, including often ignored parameters with unpredictable yet significant effects on study reproducibility and outcomes. In addition, we explore how recent developments in brain slice preparation relate to their use as models of epileptic activity.
Keywords: zvířata; orgánové kultury - kultivační techniky; Female; Male; epilepsie; Epilepsy; Animals; mozek; mužské pohlaví; mozkové vlny; ženské pohlaví; Disease Models, Animal; modely nemocí na zvířatech; Brain; Brain Waves; Organ Culture Techniques; In Vitro Techniques; techniky in vitro; poradní výbory; Advisory Committees